The toxic effect of chitosan/metal-impregnated textile to synanthropic mites - Rahel, Jozef; Jonasova, Eva; Nesvorna, Marta; Klubal, Radek; Erban, Tomas; Hubert, Jan (Pest management science, 2013)
BACKGROUND: Plasma treatment enables effective binding of chitosan film to textile fibres. Heavy metal ions such as Ag(+) adsorbed onto the chitosan coating are known to enhance toxicity to microorganisms. The acaricidal effect of chitosan and chitosan/metal adducts with Ag(+) , Zn(2+) and Cu(2+) was tested in laboratory experiments. Tested species Acarus siro, Dermatophagoides farinae, D. pteronyssinus and Tyrophagus putrescentiae are allergen producers and important pests in house dust, stored food and feed. The mortality was compared after 24 h of exposure of mites to plasma-treated textiles. RESULTS: Chitosan/Ag(+) textile caused at least 80% mortality of all species tested. Chitosan/Zn(2+) and chitosan/Cu(2+) textiles had a smaller effect on mite mortality than chitosan/Ag(+) . The conversion of chitosan/Ag(+) finishing to chitosan/Ag2 O did not influence the mortality of mites in biotests, except that of Tyrophagus putrescentiae, where the mortality decreased from 86 to 64%. CONCLUSION: The results support a great potential of chitosan/Ag(+) fibres in acaricidal materials and/or mite protective food packages.
Keywords: Acaricides; Silver; Animals; Copper; zinek; Textiles; zvířata; chitosan; akaricidy; Zinc; roztoči; Chitosan; stříbro; textilie; měď; Mites